Effects of Implementing the Short-Term Assessment of Risk and Treatability for Mechanical Restraint in a Forensic Male Population: A Stepped-Wedge, Cluster-Randomized Design - Hvidhjelm, Jacob; Brandt-Christensen, Mette; Delcomyn, Christian; Møllerhøj, Jette; Siersma, Volkert; Bak, Jesper (Frontiers in Psychiatry, 2022)
The assessment and formulation of the risk of violence and other unwanted behaviors at forensic psychiatric facilities have been attempted for decades. Structured professional judgment tools, such as the Short-Term Assessment of Risk and Treatability (START), are among the recent attempts to overcome the challenge of accomplishing these goals. This study examined the effect of implementing START in clinical practice for the most serious adverse events among the target group of severely mentally ill forensic psychiatric inpatients. Results were based on the use of mechanical restraints as an outcome. This study is a pragmatic, stepped-wedge, cluster-randomized controlled trial and was conducted over 5 years. It included eight forensic psychiatric units. Fifty out of 156 patients who had a basic aggression score of more than 0 were included in the study. We found that the rate of mechanical restraint use within the START period were 82% (relative risk [RR]=0.18), lower than those outside of the START period. Patients evaluated within the START period were also found to have a 36% (RR=0.64) lower risk of having higher Brøset Violence Checklist scores than patients evaluated outside the START period. Previous studies on START have primarily focused on validation, the predictive capability of the assessment, and implementation. We were only able to identify one study that aimed to identify the benefits and outcomes of START in a forensic setting. This study showed a significant reduction in the chance for inpatients in a forensic psychiatric facility to become mechanically restrained during periods where the START was used as risk assessment.